Perspektif Akuntansi Syariah Atas Sistem Informasi Akuntansi Penggajian Karyawan Di Cv Gunung Dono Putra Kemantren LamonganPerspektif Akuntansi Syariah Atas Sistem Informasi Akuntansi Penggajian Karyawan Di Cv Gunung Dono Putra Kemantren Lamongan - Ahmad Badrut Tamam; Dinyah Sukma (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2023)
The purpose of this study was to determine the sharia accounting perspective on the employee payroll accounting information system at CV Gunung Dono Putra Kemantren Lamongan. This study used a descriptive qualitative method using triangulation of data analysis which combines interviews, observation, and documentation. The results of this study are that the payroll accounting information system at CV Gunung Dono Putra has been running well by implementing all related functions, a network of procedures, documents and accounting records. The four components have also been implemented in accordance with sharia accounting principles in the form of responsibility, fairness, truth, piety, and honesty so as to achieve corporate prosperity.